Antiproliferative, cytotoxic and hemolytic activities of a triterpene glycoside from Psolus patagonicus and its desulfated analog - Careaga Quiroga, Valeria Pilar (2009)
Background: The major triterpene glycoside of the sea cucumber Psolus patagonicus and its desulfated analog were tested for their antiproliferative, cytotoxic and hemolytic activities, and their effect on NF-κB activation. Methods: The antiproliferative action of glycosides 1 and 2 were determined on 3 tumor cell lines. Their effect on the activation of NF-κB was evaluated by indirect immunofluorescence assay staining and the concomitant IκBα degradation was studied by Western blot. Results: Both compounds were able to suppress the growth of 3 tumor cell lines (Hep3B, MDA-MB231 and A549) and induced the activation of NF-κB, a key player linking chronic inflammation and cancer, concomitant with IκBα degradation in the A549 tumor cell line. Compounds 1 and 2 showed hemolytic activity with half maximal inhibitory concentration (IC50) values around 80 μM. Conclusions: Both glycosides showed low cytotoxic activity in A549 tumor cells in comparison with sea cucumber triterpene glycosides containing a linear tetrasaccharide chain. This could be a result of the uncommon presence of two 12α- and 17α-hydroxyl groups and a Δ7 double bond in the aglycone moiety. This aglycone functionalization may be related to their low membranolytic activity. Although glycosides 1 and 2 exert an antiproliferative effect, their mechanisms of action do not involve inhibition of NF-κB. Recently, it has been shown that diverse and new mechanisms of action are responsible for the antitumor and cytotoxic activities of marine compounds. Therefore, more extensive studies are needed to establish a mechanism of action and to deduce a clear structure-activity relationship of sea cucumber triterpene glycosides.